Association of IL28B polymorphisms with virological response to peginterferon and ribavirin therapy in children and adolescents with chronic hepatitis C. Issue 10 (7th January 2014) - Tajiri, Hitoshi; Tanaka, Yasuhito; Takano, Tomoko; Suzuki, Mitsuyoshi; Abukawa, Daiki; Miyoshi, Yoko; Shimizu, Toshiaki; Brooks, Stephen
<x xml:space="preserve">Abstract</x> Aim The objective of the current study was to find baseline predictive factors of response to therapy with pegylated interferon and ribavirin (PEG‐IFN/RBV therapy) in children and adolescents with chronic hepatitis C. Methods IL28B genotype and mutations in the core of hepatitis C virus (HCV) were analyzed in 30 patients treated with PEG‐IFN/RBV for HCV infection. The initial rate of decrease in the viral load was assessed during the first 2 weeks of treatment. Results IL28B major allele was seen more frequently in patients with sustained virologic response (SVR) than in non‐SVR patients (P < 0.001). There was no difference between these two groups in frequency of Core 70 mutation. Among patients with genotype‐1, SVR was achieved in more patients (P = 0.007) in the IL28B major allele group than in those in the minor allele group. The early decrements in the viral load (log/2 weeks) were 3.80 ± 0.86 in the genotype‐2 major allele group, 1.82 ± 0.84 in the genotype‐1 major allele group, and 0.41 ± 0.33 in the genotype‐1 minor allele group. Conclusions Among pediatric patients with HCV infection the effectiveness of PEG‐IFN/RBV therapy may be lower in the group with genotype‐1 IL28B minor alleles than in other groups with IL28B major allele. Treatment strategy should be carefully implemented in patients with IL28B unfavorable type.